PENJAMINAN MUTU PENDIDIKAN ISLAM DI SMA N 1 SERBAJADI - Suwandi Suwandi; Aulya Fahma (Universitas Islam Negeri (UIN) Sumatera Utara, 2022)
The development and management of Islamic educational institutions in achieving excellence is a matter that needs to be constantly updated and improved so that education continues to exist in responding to the challenges of the times and the needs of the wider community and the industrial world. Because education is believed to be the main foundation in building the civilization of a nation, its quality must be maintained in order to produce superior, noble and competitive governance and graduates. This study aims to reveal the position and role of quality assurance of Islamic education in Islamic religious higher education institutions. This research is a descriptive qualitative type with data collection techniques through observation, interviews and document studies at SMA N 1 Serbajadi. The results of this study indicate that the Quality Assurance of Islamic Education in SMA N 1 Serbajadi has not been fully running well and the elements in quality assurance such as education personnel, educational facilities and infrastructure, curriculum and evaluation have also not run fully in order to produce professional governance, the quality and quality of graduates who are absorbed in the community, humane services to produce outcomes in accordance with the mandate of the Act.